2017
DOI: 10.1177/1178622117728913
|View full text |Cite
|
Sign up to set email alerts
|

Coal Mining and Local Environment: A Study in Talcher Coalfield of India

Abstract: Despite government's repeated assertions for the sustainable mining extraction and development of rural and tribal communities living near the vicinity of mining areas, these have not been converted into implementable solutions. The natural resources from rural and tribal areas are being exploited to meet the ever-increasing requirements and aspirations of the affluent groups. With the above background, this article, taking both experimental and control villages into account, tried to explore the impact of coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…Talcher coalfield is situated in Brahmani valley to the north of Mahanadi river in the Talcher block of Angul district, about 120 km away from Bhubaneswar, the capital of Odisha (Mishra and Das 2017 ). Currently, 10 mining projects with an area of 15,0966 square km are operating under this coalfield.…”
Section: Coal As Economic Resources: Global and Local Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Talcher coalfield is situated in Brahmani valley to the north of Mahanadi river in the Talcher block of Angul district, about 120 km away from Bhubaneswar, the capital of Odisha (Mishra and Das 2017 ). Currently, 10 mining projects with an area of 15,0966 square km are operating under this coalfield.…”
Section: Coal As Economic Resources: Global and Local Scenariomentioning
confidence: 99%
“…The underprivileged and indigenous people like the tribal communities living in resource-rich areas become the worst affected victims of coal mining. Though they depend heavily on the ecosystem, their livelihood practices are mostly affected by mining practices (Paltasingh and Paliwal 2014 ; Mishra and Das 2017 ). It is argued that while the power-privileged people cherish all the benefits, the marginalised sections perish and bear all the brunts (Fernandes 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Around 8.7% of these affected water supplies were within the 200 feet's of active mining sites [98]Similarly, another study conducted in Jharia coal mine region (India) had also shown instability in its water table [99]. Almost all of the tube wells in the mining area (Odrisha, India) dried during the summer season [100]. Additionally in case of Bangladesh, groundwater table is highly vulnerable to coal mining with a depletion rate of >5 m (Table 3).…”
Section: Depression Of Water Table Around the Dewatered Zonementioning
confidence: 99%
“…In addition to global warming, India is simultaneously facing other prominent environmental and resource issues. These include water scarcity [35], air and water pollution [36,37], and land and ecosystem degradation [38,39]. Therefore, an integrated approach to concurrently assess and combat multiple sustainability challenges is required [38,40].…”
Section: Introductionmentioning
confidence: 99%